2016
DOI: 10.1016/j.jcv.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic choriomeningitis, Ljungan and orthopoxvirus seroconversions in patients hospitalized due to acute Puumala hantavirus infection

Abstract: a b s t r a c tBackground: The emergence and re-emergence of zoonotic and vector-borne diseases are increasing in Europe. Prominent rodent-borne zoonotic viruses include Puumala hantavirus (PUUV; the causative agent of nephropathia epidemica, NE), lymphocytic choriomeningitis virus (LCMV), and orthopoxviruses (OPV). In addition, Ljungan virus (LV) is considered a potentially zoonotic virus. Objective: The aim of this study was to compare clinical picture between acute PUUV patients with and without additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Data from this study showed that the seroprevalence of LCMV was lower (5.0%, Table ) than in our previous study conducted on 116 patients hospitalized for NE in Finland (8.5%) . Similar results have been reported in earlier serological studies of human LCMV infections in the United States America and Europe.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Data from this study showed that the seroprevalence of LCMV was lower (5.0%, Table ) than in our previous study conducted on 116 patients hospitalized for NE in Finland (8.5%) . Similar results have been reported in earlier serological studies of human LCMV infections in the United States America and Europe.…”
Section: Discussionsupporting
confidence: 88%
“…More recently, we tested for LV antibodies in 534 serum samples collected from 116 Finnish patients hospitalized for NE with serologically confirmed acute PUUV infection. Seroprevalence to LV in this panel was 47.8%, but we did not encounter any unusual or additional symptoms in patients with LV antibodies, hence it seems unlikely that exposure to LV influences NE severity. Here, LV seroprevalence tended to be higher in younger patients, increasing from 39%, in 5‐10‐year‐old patients, to 52% in 11‐20‐year‐olds (Table ) and then decreasing with age.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Slides for IFA were prepared in the laboratory, using Vero E6 cells infected with VACV. Specific human IgG were detected using standard procedures [36]. In particular, rabbit anti-human IgG conjugated with fluorescein isothiocyanate was used as a secondary antibody (Sigma-Aldrich, Inc.).…”
Section: Methodsmentioning
confidence: 99%